Automating the Generation of Microservice Architectures in Web Applications - Pavel-Cristian CRACIUN (Database Systems Journal, 2024)
The advent of microservice designs, which prioritizes enhancing deployment timelines, scalability, and flexibility, marks an advancement period in software development. This article presents a tool designed to accelerate the construction of microservice architectures. Using an intuitive interface, the solution allows users to create fundamental code and graphically construct structures, streamlining the typically laborious first coding process. By automating project documentation and scaffolding, the solution reduces resource consumption and speeds development. A comparison with Spring Initializr demonstrates a straight path from conceptual design to deployable code, underscoring this tool’s potential to revolutionize software project development.